Peranan Dinas Kehutanan Dalam MenanggulangiTindak Pidana Illegal Logging(Studi Dinas Kehutanan Dan Perkebunan Kabupaten Wonogiri) - Prabawati, Sholekha; , Dr. Natangsa Surbakti, S.H., M.Hum (2016)
The study aims to determine the punishment rules for illegal loggers on criminal law and indonesia, the barries of wonogiri forestry department in tackling illegal logging,and the efforts of wonogiri forestry department in tackling illegal logging. The method in this study used empiric juridical which is using decription. We find 5 (five) results about it, they are KUHP, Civil Law No 5 Year 1967, Civil Law No 5 Year 1990, Cicil Law No 41 Year 1999, Civil Law No 18 Year 2013. The barries in this case include a weak team, the society not conceive about forest importance, the society not conceive about the forestry rules, lack of services in forest maintenance. The efforts of this case include forest monitoring, inter-agency coordination, as an expert witness, empowerment of forest communities.